Effects of a single beach tennis session on short-term blood pressure variability in individuals with hypertension: a randomized crossover trial. Issue 3 (7th March 2022) - Domingues, Lucas Betti; Carpes, Leandro de Oliveira; Fuchs, Sandra Costa; Ferrari, Rodrigo
Abstract : Despite the importance of blood pressure (BP) variability to estimate cardiovascular risk in patients with hypertension, not all exercise modalities can reduce short-term BP variability, and no studies have measured the acute effects of recreational sports on short-term BP variability. We investigated the acute effects of a single beach tennis (BT) session on short-term BP variability in individuals with hypertension. Twenty-two participants took part in this randomized clinical trial. They were randomly allocated to a BT session and a nonexercise control session (Con). BT and Con sessions lasted 45 min. Office BP and heart rate were measured throughout the experimental sessions to calculate rate-pressure products and estimate the cardiovascular demand of BT. To determine short-term BP variability after BT and Con sessions, average real variability (ARV) of systolic BP and diastolic BP was assessed over 24 h using ambulatory BP monitoring. Compared with Con, there were lower 24-h (Δ, −0.9 ± 0.4 mmHg; P = 0.049) and daytime (Δ, −1.4 ± 0.5 mmHg; P = 0.004) ARV of diastolic BP after BT. There were no significant differences in ARV of systolic BP between Con and BT. There was a higher rate-pressure product found during BT ( P < 0.001). However, after the experimental sessions, there was no significant difference between BT and Con for the rate-pressure product under ambulatory conditions. In conclusion, a single BT session reduced daytime and 24-h diastolic BP variability in adults with hypertension. Trial registration: ClinicalTrials.gov, NCT03909308.